Intrinsic and Extrinsic Motivation Affecting Learning Effectiveness in Physical Education of Junior College Students in China - Liu, Xiaoyang (International Journal of Social Sciences and Public Administration, 2024)
The effectiveness of learning among college students in China in the domain of physical education is shaped by how they perceive intrinsic and extrinsic motivation. This study evaluates the intrinsic and extrinsic motivations of Physical education junior college students’ affecting the learning effectiveness from three universities in Guangdong, Province, China. There were 366 students chosen as participants in the study using a stratified random sampling method without making any special choices. This study is a descriptive- comparative- correlational research utilizing standard questionnaire. To ensure the valid and systematic presentation, analysis, and interpretation of the data the following statistical tools were obtained: frequency count and percentage, weighted mean calculation, ranking, standard deviation, independent sample T-tests, one way ANOVA and Pearson Moment Correlation.The study revealed that the consistent recognition of intrinsic motivations as moderately effective underscores their critical role in driving student engagement in physical education, highlighting the importance of choice, progress, meaningfulness, and competence. While extrinsic motivations are seen as moderately effective, their role is secondary to intrinsic factors, suggesting that social approval, external rewards, and competition still contribute to student motivation. The perceived effectiveness of factors such as autonomy, a supportive environment, and mastery-oriented feedback underscores their importance in enhancing learning experiences. The strong correlation between both intrinsic and extrinsic motivators with learning effectiveness emphasizes the essential link between motivation and successful learning outcomes in physical education. Based on the study’s findings, it is recommended that educators tailor motivational strategies to meet the specific needs and preferences of students, recognizing the universal value of intrinsic motivators while being mindful of individual differences, regardless of sex, specialization, or age. To improve learning outcomes, educators should provide opportunities for autonomy in decision-making, create a supportive and encouraging learning environment, and offer feedback that emphasizes mastery and improvement. Additionally, recognizing the strong connection between student motivation and learning outcomes, educators should foster both intrinsic and extrinsic motivation. This approach can enhance students’ perceived learning effectiveness, leading to improved academic performance and engagement in physical education. Implementing these strategies will enable educators to better support student motivation and success in physical education.